Propriedades fotofísicas de filmes finos de polímeros conjugados como meio ativo de ganho e aplicações em dispositivos emissores de luz (OLEDs) - Ive Silvestre de Almeida (2009)
The present work presents studies of the gain properties of a thin lm ofthe conjugated polymer Poli(2,5-bis(2'-ethyl-hexyl)-1,4-phenylenevinylene] (BEHPPV) deposited on a Si/SiO2 substrate. This conguration forms a waveguide, allowing the Amplication of Spontaneous Emission (ASE) of the material. The optical characterization of the system was performed from an experimental conguration using edge photoluminescence setup technique, in which the lm is excited by a laser shaped into a strip and the emitted light is collected from the cleaved edge of the sample. The edge emission spectra were obtained for constant lengths L of the excitation laser stripe. For each L, the laser intensity was varied from arelatively small value up to the appearance of ASE eect. A method based on the unidimensional gain equation has been developed in order to t the experimental data. The results have conrmed not only a dependence of the gain coecient on the laser intensity but also on the length L of the excitation laser stripe. We have fabricated organic light emitting diodes (OLEDs) using the polymers [Poli(2,5-bis(3',7'-dimethyl-octyloxy)-1,4-phenylene-vinylene)] (BDMO-PPV)and [Poli(9,9-dihexyluoren-2,7-diyl)-co-(9-ethylcarbazol-2,7-diyl)] (PDHF-ECz) in order to demonstrate their technological applications. We have investigated single active layers as well as more complex bilayer structures composed by these polymers. In particular, the results obtained from OLEDs based on bilayers have been interpretedconsidering eects of migration and accumulation of charge carriers between the polymers. Experimental techniques as electroluminescence (EL) and photoluminescence (PL) have been used. The characteristic current versus voltage curves were acquired for sake of comparison. The luminances of the fabricated OLEDs were also measured, enabling us to conclude that bilayer structures show higher emission efficiencies.